Advertisement Remove all ads

Simplify : 3 Xx 9^( N + 1 ) - 9 Xx 3^(2n)/3 Xx 3^(2n + 3) - 9^(N + 1 ) - Mathematics

Sum

Simplify : `[ 3 xx 9^( n + 1 ) - 9 xx 3^(2n)]/[3 xx 3^(2n + 3) - 9^(n + 1 )]`

Advertisement Remove all ads

Solution

`[ 3 xx 9^( n + 1 ) - 9 xx 3^(2n)]/[3 xx 3^(2n + 3) - 9^(n + 1 )]`

= `[ 3 xx (3^2)^(n + 1) - 3^2 xx 3^(2n)]/[ 3 xx 3^(2n + 3) - (3^2)^(n + 1)]`

= `[ 3^( 1 + 2n + 2) - 3^( 2 + 2n )]/[3^(1 + 2n + 3) - 3^( 2n + 2 )]`

= `[ 3^( 3 + 2n ) - 3^( 2 + 2n )]/[3^(4 + 2n) - 3^( 2n + 2 )]`

= `[ 3^(2n)( 3^3 - 3^2 )]/[3^(2n)(3^4 - 3^2)]`

= `[ 27 - 9 ]/[ 81 - 9 ]`

= `18/72`

= `1/4`

Concept: Solving Exponential Equations
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 9 ICSE
Chapter 7 Indices (Exponents)
Exercise 7 (C) | Q 2 | Page 101
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×